Human Resource Development in Sharia Economics: Research Map and Current Issues - Hasibuan, Faisal Umardani; Hamzali, Said (Westscience Press, 2025)
This study explores the scholarly landscape of human resource development (HRD) within the domain of Sharia economics through a bibliometric analysis using VOSviewer. Drawing data from the Scopus database covering the years 2000 to 2024, the research identifies key themes, authorship patterns, and international collaborations related to HRD in Islamic economic contexts. The co-occurrence, overlay, density, and co-authorship visualizations reveal that while Islamic economics, Islamic banking, and sharia compliance are dominant themes, HRD-specific terms remain marginal in the academic discourse. Influential authors such as Hassan M.K. and Rabbani M.R. are at the forefront of institutional and policy discussions, while Indonesia emerges as a central hub in international collaboration. However, the limited integration of HRD concepts points to a significant gap between institutional growth and human capital readiness. This study concludes by emphasizing the need for more integrated, ethically grounded, and competency-driven HRD models to support the sustainable development of Sharia-based economic systems.